2017
DOI: 10.1186/s12947-017-0107-6
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study using 3D–longitudinal strain computation in a multi-parametric approach for best selecting responders to cardiac resynchronization therapy

Abstract: BackgroundAlmost all attempts to improve patient selection for cardiac resynchronization therapy (CRT) using echo-derived indices have failed so far. We sought to assess: the performance of homemade software for the automatic quantification of integral 3D regional longitudinal strain curves exploring left ventricular (LV) mechanics and the potential value of this tool to predict CRT response.MethodsForty-eight heart failure patients in sinus rhythm, referred for CRT-implantation (mean age: 65 years; LV-ejectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Some scores, detailed above but not tested in this study, include more advanced echocardiographic data (than for instance LVEF). These are methods of great interest but still have not shown a reproducible ability to identify responders of CRT [21]. No scores to date include perioperative data such as interelectrode electrical delay or left ventricular lead positioning, in combination with preoperative variables.…”
Section: Other Scoresmentioning
confidence: 99%
“…Some scores, detailed above but not tested in this study, include more advanced echocardiographic data (than for instance LVEF). These are methods of great interest but still have not shown a reproducible ability to identify responders of CRT [21]. No scores to date include perioperative data such as interelectrode electrical delay or left ventricular lead positioning, in combination with preoperative variables.…”
Section: Other Scoresmentioning
confidence: 99%
“…Similarly, Fournet et al in their pilot study discussed the potential role of analyzing three-dimensional strain curves using automated quantification by way of computerized algorithms to predict CRT response. 29 Tao et al separately shared their observations upon using gated single-photon-emission computed tomography myocardial perfusion imaging to assess both scar burden and contractility pattern, with a U-shaped contractility pattern significantly associated with LVEF improvement versus a non-U-shaped contractility pattern. 30 Similarly, cardiac magnetic resonance imaging has also been effective in assessing scar burden, which is associated with a reduced response to CRT, as well as global ventricular dyssynchrony pattern.…”
Section: The Role Of Cardiac Imagingmentioning
confidence: 99%
“… 9 Assessment of regional mechanical function to predict CRT response seems promising. 18 , 31 , 35 , 38 Studies have shown that dyssynchronous ventricles disperse myocardial work and that modification of myocardial workload is a key factor in the reverse remodeling seen after CRT. 13 , 14 , 36 One study suggests that the so-called “wasted work”-parameter during the isovolumetric phase of the heart cycle may be a predictor.…”
Section: Introductionmentioning
confidence: 99%